2016
DOI: 10.18632/oncotarget.14247
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of exosome-mediated miR-210 transfer from hypoxic tumor cells

Abstract: Cancer cells actively release exosomes carrying specific cellular components, such as proteins, mRNA, and miRNA, to communicate with various cells in the tumor microenvironment. We visualized exosome-mediated transfer of miR-210 from hypoxic breast cancer cells to neighboring cells using a miR-210 specific reporter system. By in vitro and in vivo visualization, we found that exosomes with miR-210 were transferred to cells in the tumor microenvironment and that miR-210 was involved in expression of vascular rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
98
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(100 citation statements)
references
References 31 publications
(30 reference statements)
0
98
1
1
Order By: Relevance
“…For example, a significant increase in the exosomal miRNA‐210 of hypoxic breast cancer cells was observed both in vitro and in vivo. Uptake of hypoxic miRNA‐210‐enriched exosomes by ECs was demonstrated to upregulate vascular remodeling‐related genes, such as PTP1B and Ephrin A3, and to enhance angiogenesis …”
Section: Exosomes In Hypoxia Conditionsmentioning
confidence: 99%
“…For example, a significant increase in the exosomal miRNA‐210 of hypoxic breast cancer cells was observed both in vitro and in vivo. Uptake of hypoxic miRNA‐210‐enriched exosomes by ECs was demonstrated to upregulate vascular remodeling‐related genes, such as PTP1B and Ephrin A3, and to enhance angiogenesis …”
Section: Exosomes In Hypoxia Conditionsmentioning
confidence: 99%
“…Niemoeller et al () analysed miRNA expression levels of six malignant cancer cell lines after radiotherapy and showed that, among others, miRNA‐210, −31, and − 378 are over‐expressed. In addition, miRNA‐210‐containing exosomes establish a cross‐talk between primary cancer cells and neighbouring metastatic cells promoting tumour progression, EMT, and MET regulation, while miRNA‐31‐containing exosomes regulate reprogramming efficiency through mitochondrial metabolism (Bigagli et al , ; Jung et al , ). Interestingly, Pinweha et al () showed that miRNA‐210, −31, and − 378 inhibit SDH and/or FH expression (Table ), strongly supporting a causal link between oncometabolites and tumour repopulation.…”
Section: Oncometabolites and Tumour Repopulationmentioning
confidence: 99%
“…Exosomes that were directly labeled with Cy7 administered iv and imaged using IVIS spectrum showed a tendency to accumulate mainly in the tumor tissue and intestine. Analysis of mouse serum also indicated systemic circulation of exosomes containing miR-210 (Jung et al, 2017). Exosomes derived from mesenchymal stem cells (MSCs) have the potential for therapy of injured tissue, as they preserve some of the therapeutic characteristics and factors of their parent cells (R. C. Lai et al, 2013).…”
Section: Optical Imagingmentioning
confidence: 99%